Improving Healthcare A Dose of Competition A Report By The Federal Trade Commission and Department of Justice (July, 2004), with various Supplementary Materials - Hyman, David; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
Improving Healthcare: A Dose of Competition systematically examines the American health care system from a competition-oriented perspective. The volume surveys the performance of each major sector of the health care system, and identifies impediments to more effective competition. Improving Healthcare examines such issues as competition v. regulation, public and private sector approaches to health care financing, cross-subsidies, licensure, provider market concentration, financial and clinical integration, payment for performance, quality, pharmacy benefit managers, direct-to-consumer advertising of pharmaceuticals, certificates of need, mandates, unionization, the significance of organizational status (nonprofit v. for-profit), and the role of antitrust and consumer protection in health care. It offers concrete recommendations to improve the quality and cost-effectiveness of the American health care marketplace.
Executive Summary -- Overview/Background -- Industry Snapshot and Competition Law: Physicians -- Industry Snapshot: Hospitals -- Competition Law: Hospitals -- Industry Snapshot: Insurance and Other Third Party Payment Programs -- 6: Competition Law: Insurers -- Industry Snapshot and Competition Law: Pharmaceuticals -- Miscellaneous Subjects.
Keywords: Health informatics; Medical laws and legislation; Economic policy; Social policy; Law and economics; Economics; Economic Policy; Law and Economics; Medical Law; Health Informatics; Social Policy; Electronic books